Transcripts synthesized by RNA polymerase III can be polyadenylated in an AAUAAA-dependent manner - Borodulina, Olga R. (Cold Spring Harbor Laboratory Press, 2008)
It is well known that nearly all eukaryotic mRNAs contain a 3′ poly(A) tail. A polyadenylation signal (AAUAAA) nearby the 3′ end of pre-mRNA is required for poly(A) synthesis. The protein complex involved in the pre-mRNA polyadenylation is coupled with RNA polymerase II during the transcription of a gene. According to the commonly accepted view, only RNAs synthesized by RNA polymerase II can be polyadenylated in an AAUAAA-dependent manner. Here we report the polyadenylation of short interspersed elements (SINEs) B2 and VES transcripts generated by RNA polymerase III. HeLa cells were transfected with SINE constructs with or without polyadenylation signals. The analyses of the SINE transcripts showed that only the RNAs with the AAUAAA-signal contained poly(A) tails. Polyadenylated B2 RNA was found to be much more stable in cells than B2 RNA without a poly(A) tail.